Mathematical modelling of distribution of genes the damage of which leads to oncologic diseases in human population - Bondarenko, M. A.; Knigavko, V. G.; Gordiyenko, N. O.; Zaytseva, O. V.; Kocharova, T. P. (Biophysical Bulletin, 2016)
Carcinogenesis is subject of the research. The research aims at creating the mathematical model of carcinogenesis allowing assessing the distribution in human population of the genes which when damaged lead to oncology diseases. The main task is to build a probability mathematical model describing the quasistationary equilibrium of two contrary processes, and namely: 1) the process of reduction in population of the number of the aforesaid genes due to their mutative damage; 2) increase in population of the number of these genes due to the fact that persons with a few genes of the kind in their genotype acquire oncological diseases with higher probability at early stages of their lives and do not manage to reproduce themselves before they die, and so the growth of the total population size is more due to the reproduction of individuals with a high number of the a-genes. Assessment of the distribution of these genes in the population was carried out by determining the probability that a randomly selected individual from the population has one of the possible values (according to the literature, from 0 to 8) of the aforementioned genes.